2015
DOI: 10.1007/s12035-015-9133-2
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Reproducibility Underscore Utility of RT-QuIC for Diagnosis of Creutzfeldt-Jakob Disease

Abstract: Real-time quaking-induced conversion (RT-QuIC) allows the amplification of miniscule amounts of scrapie prion protein (PrPSc). Recent studies applied the RT-QuIC methodology to cerebrospinal fluid (CSF) for diagnosing human prion diseases. However, to date, there has not been a formal multi-centre assessment of the reproducibility, validity and stability of RT-QuIC in this context, an indispensable step for establishment as a diagnostic test in clinical practice. In the present study, we analysed CSF from 110 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(171 citation statements)
references
References 13 publications
(25 reference statements)
7
160
0
3
Order By: Relevance
“…This is highlighted by the significant progress made in the field of RT-QuIC analysis within the last several years, demonstrating its utility for the identification of prion seeding activity in a multitude of tissues, including CSF, urine, saliva, blood, brain, lymph node tissue, and nasal lavage fluid/swabs (21,38,39,47,(49)(50)(51)(52)(53)(54). Additionally, intraassay variability has proven to be low (23,61), and with the ability to run a large number of samples simultaneously, generating rapid (Ͻ24 h), quantitative results, RT-QuIC is a fast, easy, and user-friendly assay with potential for widespread application in CWD research and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…This is highlighted by the significant progress made in the field of RT-QuIC analysis within the last several years, demonstrating its utility for the identification of prion seeding activity in a multitude of tissues, including CSF, urine, saliva, blood, brain, lymph node tissue, and nasal lavage fluid/swabs (21,38,39,47,(49)(50)(51)(52)(53)(54). Additionally, intraassay variability has proven to be low (23,61), and with the ability to run a large number of samples simultaneously, generating rapid (Ͻ24 h), quantitative results, RT-QuIC is a fast, easy, and user-friendly assay with potential for widespread application in CWD research and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Following the report by Atarashi and colleagues 14) other groups have reported similar success with the RT-QuIC assay as a pre-mortem diagnostic test using CSF specimens [15][16][17] . In the study by McGuire and colleagues 16) , a blinded retrospective analysis of CSF samples from 108 patients yielded 91% sensitivity and 98% specificity, while their prospective study of 118 patients delivered 87% sensitivity and 100% specificity, with rec-huPrP evincing greater tendency to spontaneous conversion to PrP D in non-CJD cases than rec-haPrP.…”
Section: The Rt-quic As the "Next Generation" Pre-mortem Csf Diagnostmentioning
confidence: 73%
“…Using 12 CJD and 6 control CSF samples, this study additionally assessed the potential influence of storage temperatures (room temperature and +4 °C for up to 8 days; −80 °C for up to 9 years) and repeated freeze-thawing on the RT-QuIC assay with no significant adverse effects. In contrast, this study found that lysis of spiked red blood cells (RBCs) could adversely affect the sensitivity of the RT-QuIC either through spontaneous lysis over time (5,000 RBCs /µl >3 days) or if >1250 RBCs/µl were immediately sonicated 15) . In the most recent, larger collaborative study, 11 laboratories from 8 countries participated in a "blinded" ring trial of 15 CSF samples; there was perfect concordance between the laboratories for all CSF samples (McGuire et al Ann Neurol − in press).…”
Section: International Collaborative Studies To Validate the Csf Rt-qmentioning
confidence: 87%
See 1 more Smart Citation
“…The diagnostic sensitivity of RT-QuIC is between 82-96% and practically full specificity. Nonetheless, technique still not that improved to discriminate CJD subtypes in comparison to age matched healthy and non-demented controls [32][33][34][35][36]. However, recent reports also showed lower detection sensitivity in CJD subtypes interrelated to type 2 abnormal prion protein (PrPSc) (VV2, MV2 and MM2) than in typical MM1 subtype of CJD.…”
Section: Prpc and Prpscmentioning
confidence: 99%